Development of a New Scale to Assess Students’ Autodetermination At School (AAS) - Christine Sanchez; Bertrand Porro; Nathalie Blanc (European Journal of Investigation in Health, Psychology and Education, 2024)
The Autodetermination At School (AAS) hetero-evaluative scale was created and validated in a French teacher population with the aim of quantifying, in an ecological way, the commitment at school of elementary students. After establishing the scale’s face validity, AAS was tested with an exploratory factor analysis, a confirmatory factor analysis, a convergent validity analysis, a test–retest analysis and an inter-individual analysis. The EFA highlighted three distinct factors and the CFA validated the reliability of a three-factor model for AAS with relevant fits and indices. The first dimension concerns teacher perception of academic commitment, reflecting both child performance and autonomous motivation. The second and third ones reflect teacher perception of the child’s social commitment, to their peers as well as to their teacher. Consequently, AAS is a useful, reliable and robust psychometric instrument that emphases how intrinsic motivation and performance are closely linked. It also considers the importance of social child commitment at school. The inter-individual analysis revealed trends of grade, gender and school environment effects.